2018
DOI: 10.1080/18146627.2016.1251294
|View full text |Cite
|
Sign up to set email alerts
|

Harmonising the Efforts of School Nurses and Teachers in Health Promotion in Schools

Abstract: A vital facet that adds value to schools is the partnership between the departments of education and health at national level. At the heart of making this partnership effective in order to achieve its potential is the need for synchronisation of the roles of school nurses and teachers to mitigate sustainability risks. in order to investigate the harmonisation of these roles, an explorative qualitative study was conducted with school nurses and teachers in three district municipalities in two provinces of south… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Gugglberger et al (2017) stated that school health coordinators in Austria experience a lack of support alongside pressure to perform and succeed from the school leadership team. In the same vein, Kwatubana (2018) found complaints about a lack of support from school managers in South Africa. School managers were often said to be busy and did not welcome programmes that clashed with their plans.…”
Section: Resultsmentioning
confidence: 99%
“…Gugglberger et al (2017) stated that school health coordinators in Austria experience a lack of support alongside pressure to perform and succeed from the school leadership team. In the same vein, Kwatubana (2018) found complaints about a lack of support from school managers in South Africa. School managers were often said to be busy and did not welcome programmes that clashed with their plans.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the protection of individuals from environmental hazards, many activities, such as vaccination campaigns (Hoekstra et al., 2016; Irvine, 2007; King & Pappas‐Rogich, 2011; Kwatubana, 2018; Richard et al., 2010; Roden, Jarvis, Campbell‐Crofts, & Whitehead, 2016; Samarasinghe et al., 2010; Thompson et al., 2008), disease screening, contact tracing and partner notification to prevent sexually transmitted diseases (Abe et al., 2014; Sannisto & Kosunen, 2009; Thompson et al., 2008), are performed to protect individuals from biological aggression.…”
Section: Resultsmentioning
confidence: 99%
“…Some authors describe nurses' activities or partnerships within the community to address specific determinants of health, such as physical exercise and sexual or emotional health (Hernandez & Anderson, 2012; Larsson et al., 2014; Marent et al., 2018; Morrison‐Sandberg et al., 2011; Onnela et al., 2014; Ribera, McKenna, & Riddoch, 2005; Samarasinghe et al., 2010). Nurses strive to maintain sustainable relationships with other institutions at the local level, including neighbourhoods, community workers, churches, the volunteer sector, fitness centres, teachers, food service staff at schools and city councils (Heidemann et al, 2019; Kwatubana, 2018; Manasatchakun, Choowattanapakorn, Roxberg, & Asp, 2018; Marent et al., 2018; Morrison‐Sandberg et al., 2011; Muckian et al., 2017; Onnela et al., 2014; Ribera et al., 2005; Samarasinghe et al., 2010). In the hospital setting, nurses support patient involvement within the community and organise patients' clubs both inside and outside hospitals to increase emotional support from other individuals with identical pathologies (Pham & Ziegert, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…When school nurses follow the guidelines of the framework, they provide holistic care for the students within their schools. Furthermore, school nurses collaborate with teachers to ensure students are healthy enough to be able to focus and concentrate on their academic needs (Kwatubana, 2018). They routinely assess for mental health problems and plan early interventions (Bohnenkamp et al, 2015).…”
Section: Role Of School Nursesmentioning
confidence: 99%
“…These respective professions have varying training and responsibilities in the school, creating natural divisions in specialty. Considering this, research has shown that school staff do not understand the role of the school nurse and school leaders did not support their role (Kwatubana, 2018). School nurses have the responsibility to promote cooperation within the school environment by effectively educating school staff about their specialized roles.…”
Section: Implications For School Nursingmentioning
confidence: 99%